Čarovništvo – diskurz ali praksa? - Mencej, Mirjam (Studia mythologica Slavica, 2020)
This paper challenges a generally accepted view that witchcraft is always a matter of discourse, and the witch a fictitious person who is ascribed bewitchment but, in fact, performed none. It discusses the hints that point to bewitchments being, at least occasionally, a matter of practice and reality, and a “witch” indeed a practitioner of acts, perceived as harmful. It also challenges the etic difference between the “natural” and “supernatural” acts in the context of witchcraft accusations and argues that there is no clear difference between the former and the latter for people thinking within a witchcraft discourse.